2015
DOI: 10.1590/1414-431x20144250
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin protects against damage to spatial learning and memory ability in mice with chronic alcohol poisoning

Abstract: We evaluated the effect of puerarin on spatial learning and memory ability of mice with chronic alcohol poisoning. A total of 30 male C57BL/6 mice were randomly divided into model, puerarin, and control groups (n=10 each). The model group received 60% (v/v) ethanol by intragastric administration followed by intraperitoneal injection of normal saline 30 min later. The puerarin group received intragastric 60% ethanol followed by intraperitoneal puerarin 30 min later, and the control group received intragastric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
(20 reference statements)
0
6
1
Order By: Relevance
“…After the 6-week treatment period, training was carried out for 5 days. The results revealed that escape latency was prolonged, compared with control mice [39]. The discrepancy between previous reports and the current results may have been caused by differences in the ethanol treatment method (free access drinking vs intraperitoneal injection) and/ or the different concentration of ethanol used.…”
Section: Author Contributionscontrasting
confidence: 96%
“…After the 6-week treatment period, training was carried out for 5 days. The results revealed that escape latency was prolonged, compared with control mice [39]. The discrepancy between previous reports and the current results may have been caused by differences in the ethanol treatment method (free access drinking vs intraperitoneal injection) and/ or the different concentration of ethanol used.…”
Section: Author Contributionscontrasting
confidence: 96%
“…Early treatment with puerarin can effectively reduce oxidative stress damage and iron death after SAH. Previous studies showed that puerarin attenuated learning and memory impairments, as well as inhibiting oxidative-stress damage in an Alzheimer’s disease model [ 45 ] and chronic alcohol poisoning model [ 46 ]. Our study also found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Asparaginate (Asp) and Glu are excitatory amino acids and Gly and GABA are inhibitory amino acids, which play important roles in maintaining the balance of excitation and inhibition in the central nervous system (Luo et al, 2011;Wang et al, 2014). Changes in the level of central amino acids in AD, especially the imbalance between Glu and GABA, are key factors leading to neuron injury (Cui et al, 2015). In our study, cerebroprotein hydrolysate reduced the level of Glu and the ratio of Glu/GABA in the brain tissue of mice to regulate the Glu/GABA learning and memory regulation system and reduce the excitotoxicity of Glu, which may be one of the mechanisms through which cerebroprotein hydrolysate reduced the learning and memory impairment of the mice.…”
Section: Discussionmentioning
confidence: 99%